Copyright callouts and the promise of creator-driven platform governance - Blake Hallinan; C. J. Reynolds; Omer Rothenstein (Internet Policy Review, 2024)
Responding to frustrations with the enforcement of copyright on YouTube, some creators publish videos that discuss their experiences, challenge claims of infringement, and critique broader structures of content moderation. Platform callouts, or public complaints about the conduct of or on platforms, are one of the primary ways creators challenge the power imbalance between users and corporations. Through an analysis of 135 videos, we provide a rich empirical account of how creators publicly define the problem of copyright enforcement, propose solutions, and attribute responsibility to other creators, the platform, and external actors like media conglomerates. Creators criticise the prevalence of “false” copyright claims that ignore fair use or serve ulterior motives like harassment, censorship, and financial extortion, as well as the challenges of communicating with the platform. Drawing inspiration from organisational theory, we differentiate horizontal and vertical callouts according to the institutional positioning of the speaker and target. Horizontal callouts, or public complaints between peers, offer a mechanism for community self-policing, while vertical callouts, or public complaints directed towards organisations, provide a mechanism for influencing centralised content moderation policies and practices. We conclude with a discussion of the benefits and limitations of callouts as a strategy of creator-driven platform governance.
Keywords: K; L; 340; Copyright; Creators; Norms; Platform governance; YouTube